Media Framing of COVID-19 Crisis in Print Media (Indian Journal of Mass Communication and Journalism (IJMCJ), 2024)
Since the coronavirus outbreak, the Media houses have focused on the health crisis fittingly. The news of the pandemic spread faster than the virus itself. The impact of media does not only originate with what information is being disseminated but also how it is framed. It gives Mass Media the credit for forming Public Opinion. This study aims to determine and compare the dominant frames in coverage of COVID-19 news. Based on readership and popularity, two English and two Hindi newspapers are selected. The study, descriptive in nature, uses Content Analysis as a tool of analysis. With the deductive approach, the researcher considered pre-determined frames (extracted from the previous literature) analyzed and compared the stories according to them. The time frame of this study was two months, starting from April 1, when the second wave in India intensified, to May 31, 2021. The unit of analysis included all articles, features, and columns published within the time frame. It was discovered that the Hope frame (18.4%) and Fear frame (16.8%) dominated the overall study. It was also found that there were similarities and differences in framing used by both English and Hindi newspapers.